Ruptured Rudimentary Horn Pregnancy: Delayed Diagnosis - Ghotra, Maninder K (Cureus, 2021)
Developmental anomalies of the genital tract result from defective fusion and absorption of various parts of Mullerian ducts in fetal life. Rudimentary horn pregnancy is a rare occurrence of one in 76,000 and one in 160,000. We present a case of a 24-year-old primigravida with ruptured rudimentary horn pregnancy initially managed in the line of an intrauterine pregnancy with severe anemia. Hemodynamic instability made us suspect ruptured rudimentary horn pregnancy and lifesaving laparotomy was performed for the same. A 1.5-liter hemoperitoneum was encountered with a right ruptured rudimentary horn. Multiple adhesions were present with necrotic tissue adherent and clumped together as tubo ovarian mass. Resection of the rudimentary horn was performed. We report this case to emphasize the need to consider rare uterine anomalies as a possibility in patients presenting with acute abdomen in early pregnancy. Obstetricians should consider these rare entities in the differential diagnosis to provide efficient management of these cases.